Manipulation of cytokine secretion in human dendritic cells using glycopolymers with picomolar affinity for DC-SIGN. Issue 10 (24th August 2017) - Mitchell, Daniel A.; Zhang, Qiang; Voorhaar, Lenny; Haddleton, David M.; Herath, Shan; Gleinich, Anne S.; Randeva, Harpal S.; Crispin, Max; Lehnert, Hendrik; Wallis, Russell; Patterson, Steven; Becer, C. Remzi
Abstract : Dendritic cells bridge the innate and adaptive immune systems and they can be manipulated by star shaped glycopolymers. Abstract : The human C-type lectin DC-SIGN (CD209) is a significant receptor on the surface of dendritic cells (DCs) – crucial components of host defense that bridge the innate and adaptive immune systems. A range of linear glycopolymers, constructed via controlled radical polymerization techniques have been shown to interact with DC-SIGN with affinities in the physiologically active range. However, these first generation glycopolymers possess limited structural definition and their effects on DCs were not known. Here we report the development of star-shaped mannose glycopolymers with the aim of targeting the clustered domain arrangement of DC-SIGN and these were shown to bind with picomolar affinity. Increased secretion of IL-10 with simultaneous decrease in secreted IL-12p70 occurred in activated DCs incubated with star-shaped glycopolymers – a cytokine secretion pattern characteristic of wound-healing tissue environments. Incorporating stellar architecture into glycopolymer design could be key to developing selective and very high-affinity therapeutic materials with distinct immunomodulatory and tissue repair potential.